Perinatal Resveratrol Supplementation to Spontaneously Hypertensive Rat Dams Mitigates the Development of Hypertension in Adult Offspring. Issue 5 (May 2016) - Care, Alison S.; Sung, Miranda M.; Panahi, Sareh; Gragasin, Ferrante S.; Dyck, Jason R.B.; Davidge, Sandra T.; Bourque, Stephane L.
Abstract : This study was undertaken to determine whether perinatal maternal resveratrol (Resv)—a phytoalexin known to confer cardiovascular protection—could prevent the development of hypertension and improve vascular function in adult spontaneously hypertensive rat offspring. Dams were fed either a control or Resv-supplemented diet (4 g/kg diet) from gestational day 0.5 until postnatal day 21. Indwelling catheters were used to assess blood pressure and vascular function in vivo; wire myography was used to assess vascular reactivity ex vivo. Perinatal Resv supplementation in dams had no effect on fetal body weights, albeit continued maternal treatment postnatally resulted in growth restriction in offspring by postnatal day 21; growth restriction was no longer evident after 5 weeks of age. Maternal perinatal Resv supplementation prevented the onset of hypertension in adult offspring (−18 mm Hg; P =0.007), and nitric oxide synthase inhibition (with L-NG-nitroarginine methyl ester) normalized these blood pressure differences, suggesting improved nitric oxide bioavailability underlies the hemodynamic alterations in the Resv-treated offspring. In vivo and ex vivo, vascular responses to methylcholine were not different between treatment groups, but prior treatment with L-NG-nitroarginine methyl ester attenuated the vasodilation in untreated, but not Resv-treated adult offspring, suggesting a shift toward nitric oxide–independent vascular control mechanisms in the treated group. Finally, bioconversion of the inactive precursor big endothelin-1 to active endothelin-1 in isolated mesenteric arteries was reduced in Resv-treated offspring (−28%; P <0.05), and this difference could be normalized by L-NG-nitroarginine methyl ester treatment. In conclusion, perinatal maternal Resv supplementation mitigated the development of hypertension and causes persistent alterations in vascular responsiveness in spontaneously hypertensive rats. Abstract : Supplemental Digital Content is available in the text.